Using impact chains for assessing local climate risk—A case study on impacts of extended periods of fluvial low waters and drought on a metropolitan region - Lückerath, Daniel; Rome, Erich; Milde, Katharina (Frontiers in Climate, 2023)
As the climate crisis accelerates, the resilience of Europe’s ageing critical infrastructure systems shifts more and more into focus. However, the rising interconnectedness of critical infrastructure systems and the dependency of their operation on multiple stakeholders makes approaches that target the resilience of isolated infrastructures insufficient and might even result in a decrease of the resilience of the whole system. This need for more resilience thinking in interconnected infrastructure systems has resulted in advances in risk analyses of supply chains and analyses of interdependencies in infrastructure systems from a Critical Infrastructure Protection/Resilience perspective. However, results from such analyses on the level of interconnected infrastructure systems have seldomly be broken down to the level of individual corporate value chains, a necessity as national/regional resilience efforts need to be supported on the local level. In this paper we therefore propose a novel approach for value chain climate vulnerability and risk analysis that combines a participatory, indicator-based approach with a semi-quantitative risk matrix approach to allow linking analyses from national to local scale and supports economic assessment of climate change impacts for individual businesses. This approach has been developed and prototypically applied in a case study in a German metropolitan area located at the Rhine River. The results allow to identify where along the dependency chains of interconnected infrastructure systems, hazards and impacts might manifest, which cascading (economic) impacts result on the level of individual infrastructure operators, and where resilience measures should be taken to be most effective and (cost) efficient.